2017
DOI: 10.1021/acschemneuro.7b00245
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Regulates Amyloid Beta 1–42 Production with Protein Disulfide Isomerase A3

Abstract: The challenge of understanding the biology of neuronal amyloid processing could provide a basis for understanding the amyloid pathology in Alzheimer's disease (AD). Based on our previous studies, we have suggested that AD might be the consequence of a hormonal imbalance in which the critical hormone is vitamin D. The present study primarily focused on the creation of a condition that prevents the genomic or nongenomic action of vitamin D by disrupting vitamin D receptors (VDR or PDIA3/1,25MARRS); the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 60 publications
3
37
0
Order By: Relevance
“…Therefore, we labelled VDR and PDIA3/1,25MARRS on the surface of living neuronal cells and determined that VDR was abundantly localized on the neuronal membrane. Note that we have confirmed the specificity of the anti-VDR antibody which was used in immunofluorescent labeling and cell surface staining, in our previous study [ 9 ]. The presence of VDR on the plasma membrane was also confirmed in SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Therefore, we labelled VDR and PDIA3/1,25MARRS on the surface of living neuronal cells and determined that VDR was abundantly localized on the neuronal membrane. Note that we have confirmed the specificity of the anti-VDR antibody which was used in immunofluorescent labeling and cell surface staining, in our previous study [ 9 ]. The presence of VDR on the plasma membrane was also confirmed in SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 84%
“…The results of our previous study [ 9 ] led to questions about the VDR-dependent regulation of APP processing proteins. One potential regulatory mechanism was transcriptional regulation by VDR [ 9 ], and the other was the possible rapid response (RR) activity of the VDR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that vitamin D increases the AB clearance by the blood-brain barrier, increasing its brain-to-blood efflux though both genomic and non-genomic action [57,58]. Moreover, in vitro primary cultures of cortical neurons show that vitamin D is directly implicated in the production of Aβ and can downregulate its expression [59]. Several genes involved in the pathogenesis of AD have a vitamin D responding element within their sequences [60].…”
Section: Vitamin D and Cognitive Health: From Bench To Bedsidementioning
confidence: 99%